Inclusive Mentorship Support Provided by Primary School Teachers to Early Childhood and Primary Education Student-Teachers during Teaching Practice (UNIZIK Journal of Educational Management and Policy, 2025)
The challenges in the implementation of inclusive education in developing nations reflect teachers’ insufficient skills in teaching children with special education in regular schools. Professional exposure and practical experience of teachers have been noted to be significant in inclusive education. To hone these skills, mentorship in inclusive education has become essential for developing inclusive teaching competence, particularly among student-teachers who are novice practitioners. There is dearth of studies that are devoted to understanding specific mentoring support for inclusive education given to student-teachers. Consequently, this qualitative research design was employed, involving 20 student-teachers to explore inclusive mentorship support provided by primary school teachers during the teaching practice exercise. Using thematic content analysis, themes that emerged include variability in the provisions of mentorship during teaching practice, structural concerns in the provisions of mentorship during teaching practice, true inclusive mentorship programmes, development of professional confidence and attitudinal change, practical pedagogical guidance, support for learners with special education needs (SENs) and use of inclusive teaching strategies. The findings indicate that mentorship provision varied significantly across student-teachers, underscoring the need for more structured, intentional, and policy-driven mentorship frameworks within teaching practice programmes. Implications were highlighted.
Keywords: Inclusive Education, Mentorship, Special Education Needs, Student-teachers, Teacher Education